2008
DOI: 10.1128/jvi.01319-08
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Chimpanzee T-Cell Activation and Simian Immunodeficiency Virus/Human Immunodeficiency Virus Susceptibility Achieved via Antibody-Mediated T-Cell Receptor/CD3 Stimulation Is a Function of the Anti-CD3 Antibody Isotype

Abstract: While human immunodeficiency virus type 1 (HIV-1) infection is associated with hyperimmune activation and systemic depletion of CD4؉ T cells, simian immunodeficiency virus (SIV) infection in sooty mangabeys or chimpanzees does not exhibit these hallmarks. Control of immune activation is thought to be one of the major components that govern species-dependent differences in the disease pathogenesis. A previous study introduced the idea that the resistance of chimpanzees to SIVcpz infection-induced hyperimmune ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
(24 reference statements)
4
6
0
Order By: Relevance
“…This dose response parallels previous findings, which showed that chimpanzee T cells were able to proliferate in response to anti-CD3 Abs, but to a lesser degree than human T cells at the doses tested (56). We even found one anti-CD3 Ab clone, SK7, which results only in human but not chimpanzee T cell proliferation, despite high doses tested (Table I).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…This dose response parallels previous findings, which showed that chimpanzee T cells were able to proliferate in response to anti-CD3 Abs, but to a lesser degree than human T cells at the doses tested (56). We even found one anti-CD3 Ab clone, SK7, which results only in human but not chimpanzee T cell proliferation, despite high doses tested (Table I).…”
Section: Resultssupporting
confidence: 90%
“…However, as the dose of anti-CD3 was increased, chimpanzee T cells were eventually able to respond equally. This finding is independent of the binding affinity of the anti-CD3 Abs to human and chimpanzee T cells, which was found to be comparable by flow cytometry (data not shown), and is consistent with the sequences of the CD3ε ectodomain, the subunit recognized by anti-CD3 Abs, that are known to be identical in human and chimpanzee but for a single serine-glycine substitution at 68 aa (56). In addition, this is independent of the levels of expression of CD28 on human and chimpanzee T cells, which has previously been shown to be similar (39).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Siglec-5 manipulation switched the species-type response to T-cell receptor (TCR) stimulation. This species difference may be a factor in Tcell-mediated diseases, including the much milder chimpanzee disease from HIV-1 and hepatitis B or C (94), and the apparent lack of spontaneous rheumatoid arthritis and bronchial asthma. These differences in immunoreactivity could involve the weaker expression of CD33rSiglecs of humans, relative to great apes (93).…”
mentioning
confidence: 99%
“…We first evaluated a stimulation protocol using anti-CD3 or a combination of anti-CD3 + anti-CD28 monoclonal antibodies (mAbs) and the results were recently reported (Bibollet-Ruche et al, 2008). We found that not all anti-CD3 mAb isotype were equally capable of stimulating chimpanzee T cells.…”
Section: Resultsmentioning
confidence: 99%